KS3 success workbook : Mathematics SATs : levels 5-8 - "Mapp, Fiona C." (Letts London, 2007)
Covers what students need to know for Key Stage 3. Each double page spread in this title includes three sections: warm-up multiple choice questions to get your brain cells ticking, quiz-style short-answer questions to put revision into practice, and SATs-style questions to give students plenty of practice for the all-important exams.